Chemistry Students' Mathematics Ability and Their Understanding of Buffer Solution - Habiddin Habiddin; Irene Lusita Nagol (Postgraduate, University of Mataram, 2023)
Mathematics's role in solving chemical phenomena has been well known. Basic mathematical operations such as integral, logarithm and differentiations are the tools for communicating chemistry concepts. This paper describes the effect of chemistry students' mathematical ability on understanding buffer solutions. 56 First-year university chemistry students at a public University in Malang, East Java, taking basic chemistry modules involved in this study. The respondents participated on a voluntary basis after getting a piece of comprehensive information about the study. An equivalent basic mathematical skill test (BMST) and Buffer Solution Test (BST) was implemented for data collection. This study found a positive correlation between students' mathematical ability and success in answering relevant buffer solution questions. The contribution of mathematical knowledge in predicting chemistry students' success in answering relevant buffer solution questions was also essentially high. Â Â Â